Magnetıc Forces In Orthodontıc Treatment Of Anterıor Openbıte: The Comparıson Of Avc Applıance Wıth A New Magnetıc Openbıte Corrector Devıce (Two Case Reports) - Eray Erdoğan (Galenos Yayinevi, 1995)
In the orthodontic teratment of anterior openbite, posterior teeth intrusion is recommended for stabilization reasons and for some clinical needs. The intrucive effect of the rare earth magnets on the posterior teeth was shown in many studies. Yet, some of the previous appliance design causes some adverse effects like "latero-gnathies" after the openbite correction due to the magnet configuration. The patinets are generally complaining because of their bulky dimensions and hygiene difficulties. One of the first magnetic device in anterior openbite correction. ACV (Active Vertical Corrector) was tried in Orthodontic Department of Geneva University in a case. As the problems quoted above were observed, a new magnetic openbite corrector device having the similar principles was designed. In this new design, the appliance composed of metallic and acrylic anchorage units on the posterior teeth was a removable orthodontic device contrarily to the previous designs and including two magnets lingually and buccally. on each posterior bite block. As the occlusal surfaces of the posterior teeth were free of the acrylic resin, the upper and lower parts of the appliance did not have any effect on the mandibular rest position and it could be considered as less bulky. The repulsion force was generated from the north poles the upper and lower magnets was about 350 grams per side when the magnets had 1 mm of air gap in the maximum contact of the upper and lower bite blocks. The lateral guidance of mandible was realized by the repulsion force between one of the buccal magnet on the lower arch and the lingual one on the upper arch in one side; vice versa. In this study, the advantages and the disadvantages of this new magnetic openbite corrector device are discussed compared to AVC on two cases having one of these appliances.